Freezing diluted bovine serum albumin standards does not significantly affect standard curves - Rachelle Sheets; Bhavik Rajaboina; Caitlin E. Bromberg; Liam P. Curtin; Mitchell L. Haddock; Phillip Stafford; Theresa Currier Thomas; Adrienne C. Scheck (BioTechniques)
Total protein isolation followed by quantitation using a colorimetric method, such as the bicinchoninic acid (BCA) assay is a common laboratory protocol. Protein concentrations are determined by comparing extracted samples to a standard curve generated from serial dilutions of a reference protein, such as bovine serum albumin (BSA). This study aimed to identify the most reproducible and accurate method for quantifying protein concentrations in an experimental series over time. We analyzed the effect of serial freeze-thaws, inter-person and intra-person variability in standard preparation and assay execution. Absorbance was measured at 565 nanometers (nm) using an Epoch Microplate Spectrophotometer (Agilent Technologies, Inc., Santa Clara, CA) with Gen5 Data Analysis software. The most consistent and accurate method for determining the protein concentrations over time is to prepare a large batch of diluted BSA standards, aliquot them into small portions, and store them frozen.